Toll like receptors in self-recovering hepatitis E patients with or without pregnancy - Arya, Ravi P.; Arankalle, Vidya A. (Human immunology, 2014)
Hepatitis E virus (HEV) causes high mortality among pregnant women. Pathogenesis of HEV, especially during pregnancy, is poorly understood. Our aim was to assess the role of Toll-like-receptors (TLRs) in hepatitis E patients with pregnancy (Antenatal care, ANC) or without pregnancy (non-ANC). The patient categories included acute-phase, non-ANC (n=46) and ANC patients (2nd/3rd trimesters, n=13) and non-ANC patients (n=31) during convalescence. Controls included apparently healthy non-ANC (n=30) and ANC subjects in the first (n=10) and later (2nd/3rd, n=20) trimesters. TLR2/TLR3/TLR4/TLR7/TLR8 levels were determined by flow-cytometry. Cytokine responses induced by TLR-specific-ligands-stimulated-PBMCs from ANC/non-ANC-patients and TLR-signaling-molecules (non-ANC-patients) were measured. PBMCs were used to assess gene expression levels by TaqMan-Low-Density-Array. Compared to the temporal activation of TLR4/TLR7/TLR8 at protein and mRNA levels, the ANC-patients and controls exhibited reduced TLRs indicative of impaired TLR response. Stimulation of PBMCs with TLR-specific ligands led to the induction of type-I interferons, IFNβ by the non-ANC group and IFNα by the ANC category. Involvement of MyD88-independent (TLR3/TLR4) and MyD88-dependent (TLR4/TLR7/TLR8) pathways and association of TLR4/TLR7/TLR8 with recovery was documented in the non-ANC-patients. Except for robust type-I-interferon response, HEV infection could not modulate pregnancy-related diminished immune response. The results have implications in the understanding of HEV pathogenesis.